Changes between Version 9 and Version 10 of u/johannjc/scratchpad4
- Timestamp:
- 09/30/15 17:18:47 (9 years ago)
Legend:
- Unmodified
- Added
- Removed
- Modified
-
u/johannjc/scratchpad4
v9 v10 58 58 59 59 we get expressions for 60 $\phi' = \frac{\left ( \phi-\psi\lambda \right )}{\psi \left (\lambda+1 \right )} $ 60 61 61 $B_j = \ frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} \partial_i n b_i b_j $62 $B_j = \phi' C_j $ 62 63 63 64 $C_j = \kappa_\parallel \psi \partial_i n b_i b_j $ 64 65 65 $D_{ij}=\ frac{\kappa_\parallel \left ( \phi-\psi\lambda \right )}{\lambda+1} n b_i b_j$66 $D_{ij}=\phi'E_{ij}$ 66 67 67 68 $E_{ij} = \kappa_\parallel \psi n b_i b_j $ … … 85 86 where 86 87 87 $\alpha_0 = -\frac{ 1}{\Delta t} -\frac{2E_{jj}}{\Delta x^2}T_0^\lambda$88 $\alpha_0 = -\frac{2E_{jj}\Delta t}{\Delta x^2}T_0^\lambda$ 88 89 89 $\alpha_{\pm j} = \pm C_jT^\lambda_{\pm \hat{j}} + \frac{E_{jj}}{\Delta x^2}T_{\pm \hat{j}}^\lambda$90 $\alpha_{\pm j} = \pm \frac{C_j \Delta t}{2 \Delta x} + \frac{E_{jj}\Delta t}{\Delta x^2}$ 90 91 91 $\alpha_{\pm i, \pm j} = \pm \pm \frac{E_{ij}}{4 \Delta x^2}T^\lambda_{\pm \hat{i} \pm \hat{j}}$ 92 93 $\beta = -\frac{T_0}{\Delta t} \pm \frac{B_j}{2 \Delta x} T^{\lambda+1}_{\pm \hat{j}} \pm \pm \frac{D_{ij}}{4 \Delta x^2} T^{\lambda+1}_{\pm \hat{i} \pm \hat{j}}\left ( 1 - \delta_{ij} \right ) + \frac{D_{jj}}{\Delta x^2} T^{\lambda+1}_{\pm \hat{j}} - 2 \frac{D_{jj}}{\Delta x^2}T^{\lambda+1}_0$ 92 $\alpha_{\pm i, \pm j} = \pm \pm \frac{E_{ij}\Delta t}{4 \Delta x^2}$